APPLICATION OF COOPERATIVE LEARNING METHOD OF STUDENT TEAM ACHIEVEMENT DIVISION MODEL TO IMPROVE ARABIC LANGUAGE LEARNING OUTCOMES FOR CLASS X STUDENTS AT MADRASAH ALIYAH DARUL FIKRI SIDOARJO: Penerapan Metode Pembelajaran Kooperatif Model Student Team Achievement Division untuk Meningkatkan Hasil belajar Siswa Kelas X di Madrasah Aliyah Darul Fikri Sidoarjo - Destantya Asa Nusantara Adi; Najih Anwar (Journal for Technology and Science, 2024)
This article aims to find out how the cooperative learning method of the student team achievement division model is applied in Arabic language subjects and the effectiveness of the cooperative learning method of the student team achievement division model on the Arabic language learning outcomes of class X students at Madrasah Aliyah Darul Fikri Sidoarjo. This article uses classroom action research (PTK) carried out using qualitative and quantitative approaches. A qualitative approach was taken to analyze changes in students during the implementation of actions until changes occurred, namely by conducting observations, interviews and documentation. A quantitative approach was taken to determine the effectiveness of learning strategies on student learning outcomes. The population taken by the author was all students in class X of the Madrasah Aliyah Darul Fikri religious program (PK), totaling 18 students. The results of this research are the cooperative learning method using the Student Team Achievement Division model, which is carried out by dividing students with diverse Arabic language mastery into one group to help each other understand the learning material and after data processing it was found that the Cooperative Learning Method using the Student Team Achievement Division model was improving students' Arabic learning outcomes as evidenced by Increased percentage of student absorption rate